Erectile dysfunction predicts mortality in middle-aged and older men independent of their sex steroid status. (14th April 2022) - Antonio, Leen; Wu, Frederick C W; Moors, Hannes; Matheï, Cathy; Huhtaniemi, Ilpo T; Rastrelli, Giulia; Dejaeger, Marian; O'Neill, Terence W; Pye, Stephen R; Forti, Gianni; Maggi, Mario; Casanueva, Felipe F; et al.
Abstract: Background: erectile dysfunction is associated with mortality, whereas the association between low testosterone (T) and higher mortality remains controversial. Sexual dysfunction and low T often coexist, but the relative importance of sexual symptoms versus low T in predicting mortality is not known. We studied the interrelationships between sex steroids and sexual symptoms with all-cause mortality in a large prospective cohort of European men. Design: survival status was assessed in 1, 788 community-dwelling men, aged 40–79, who participated in the European Male Ageing Study (EMAS). Sexual symptoms were evaluated via a validated questionnaire (EMAS-SFQ). Sex steroids were measured by mass spectrometry. Cox proportional hazard models were used to study the association between hormones, sexual symptoms and mortality. Results: about 420 (25.3%) men died during a mean follow-up of 12.6 ± 3.1 years. Total T levels were similar in both groups, but free T was lower in those who died. Men with three sexual symptoms (erectile dysfunction, reduced morning erections and lower libido) had a higher mortality risk compared with men with none of these symptoms (adjusted hazard ratio (HR) and 95% confidence intervals: 1.75 (1.28–2.40, P  = 0.001)). Particularly, erectile dysfunction and poor morning erections, but not lower libido, were associated with increased mortality (HR 1.40 (1.13–1.74, P  = 0.002), 1.28 (1.04–1.59, P  = 0.023) and 1.12 (0.90–1.39, P  = 0.312), respectively). Further adjusting for total T, free T or oestradiol did not influence the observed risk. Conclusions: sexual symptoms, in particular erectile dysfunction, predict all-cause mortality independently of sex steroids and can be an early warning sign of a poor health status.